Enhancement of experimental ulcerative colitis by immunization with Bacteroides vulgatus. - Onderdonk, A B (1983)
Previous studies with the guinea pig model for ulcerative colitis have shown that the inducing agent, carrageenan, does not provoke ulcerations in germfree guinea pigs, but animals monoassociated with Bacteroides vulgatus develop cecal ulcerations when fed carrageenan. In an effort to define the role of B. vulgatus in this model system, conventional guinea pigs were immunized with B. vulgatus before carrageenan treatment. Immunized animals developed both circulating antibody and positive skin tests for the homologous antigen. A comparison of B. vulgatus-immune and nonimmune carrageenan recipients after 30 days of carrageenan treatment revealed ulcerations of the ceca and large intestine in both groups, but the immune group developed more severe lesions than the nonimmune group. The most severe intestinal lesions were detected in B. vulgatus-immune animals fed both carrageenan and daily doses of viable B. vulgatus. Immune recipients of B. vulgatus alone did not develop ulcerations, but showed histological evidence of intestinal inflammation. Lesions observed in B. vulgatus-immune animals were most severe in the colon and rectum, in contrast to more severe cecal lesions detected in nonimmune carrageenan recipients. Similar experiments with Bacteroides fragilis as an antigen for immunization showed no difference between immune and nonimmune groups. These results suggest that immunization with B. vulgatus enhances the severity of carrageenan-induced colitis.